Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1088/1402-4896/ac6707
|View full text |Cite
|
Sign up to set email alerts
|

Real-time fuzzy-pid synchronization of memristor-based chaotic circuit using graphical coded algorithm in secure communication applications

Abstract: The main goal of this study is to implement real-time synchronization of a memristor-based chaotic circuit for secure communication on LabVIEW virtual instrument environments. Memristors can be used in chaotic circuits because of their nonlinear behavior. In this paper, an application for secure communication systems is proposed by using the chaotic property of the memristor. Phase portraits, Lyapunov exponential spectrum, and bifurcation diagrams of the memristor-based chaotic circuit were investigated. A Fuz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Concurrently, researchers have also found that the characteristics of chaotic systems, such as ergodicity, unpredictability, extreme sensitivity to initial conditions, and pseudo-randomness, are strikingly similar to those of cryptography. Consequently, chaotic systems have found widespread applications in information security, including digital image encryption [13][14][15] and secure communication [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, researchers have also found that the characteristics of chaotic systems, such as ergodicity, unpredictability, extreme sensitivity to initial conditions, and pseudo-randomness, are strikingly similar to those of cryptography. Consequently, chaotic systems have found widespread applications in information security, including digital image encryption [13][14][15] and secure communication [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, there has been a great interest in chaos phenomena due to their important applications in several areas. Cryptography [1,2], biology [3,4], ecology [5,6], memristors [7,8], lasers [9,10], neural networks [11,12], finance [13,14], secure communications [15][16][17] are some well-known fields where the chaotic systems are applied in practice. Hyperchaotic systems are defined as continuous-time chaotic systems that exhibit what is called sensitive dependence on initial conditions with more than one positive Lyapunov exponent.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, further research into the dynamics of memristive systems is warranted [23][24][25][26][27][28]. Several studies have been published in recent years on memristor-based chaotic systems and their applications in image encryption [29][30][31][32][33][34]. Chaotic systems, such as the logistic map, Lorenz system, and Chua circuit, are the focus of cryptography research in the literature [35][36][37].…”
Section: Introductionmentioning
confidence: 99%